Bi-directional regulation of AIMP2 and its splice variant on PARP-1-dependent neuronal cell death; Therapeutic implication for Parkinson's disease - Min Hak Lee; Ki-Hwan Um; Seok Won Lee; Ye Ji Sun; Da-Hye Gu; Young Ok Jo; Sung Hyun Kim; Wongi Seol; Hyorin Hwang; Kyunghwa Baek; Jin Woo Choi (Acta Neuropathologica Communications, 2024)
Abstract Background Parthanatos represents a critical molecular aspect of Parkinson's disease, wherein AIMP2 aberrantly activates PARP-1 through direct physical interaction. Although AIMP2 ought to be a therapeutic target for the disease, regrettably, it is deemed undruggable due to its non-enzymatic nature and predominant localization within the tRNA synthetase multi-complex. Instead, AIMP2 possesses an antagonistic splice variant, designated DX2, which counteracts AIMP2-induced apoptosis in the p53 or inflammatory pathway. Consequently, we examined whether DX2 competes with AIMP2 for PARP-1 activation and is therapeutically effective in Parkinson’s disease. Methods The binding affinity of AIMP2 and DX2 to PARP-1 was contrasted through immunoprecipitation. The efficacy of DX2 in neuronal cell death was assessed under 6-OHDA and H2O2 in vitro conditions. Additionally, endosomal and exosomal activity of synaptic vesicles was gauged in AIMP2 or DX2 overexpressed hippocampal primary neurons utilizing optical live imaging with VAMP-vGlut1 probes. To ascertain the role of DX2 in vivo, rotenone-induced behavioral alterations were compared between wild-type and DX2 transgenic animals. A DX2-encoding self-complementary adeno-associated virus (scAAV) was intracranially injected into 6-OHDA induced in vivo animal models, and their mobility was examined. Subsequently, the isolated brain tissues were analyzed. Results DX2 translocates into the nucleus upon ROS stress more rapidly than AIMP2. The binding affinity of DX2 to PARP-1 appeared to be more robust compared to that of AIMP2, resulting in the inhibition of PARP-1 induced neuronal cell death. DX2 transgenic animals exhibited neuroprotective behavior in rotenone-induced neuronal damage conditions. Following a single intracranial injection of AAV-DX2, both behavior and mobility were consistently ameliorated in neurodegenerative animal models induced by 6-OHDA. Conclusion AIMP2 and DX2 are proposed to engage in bidirectional regulation of parthanatos. They physically interact with PARP-1. Notably, DX2's cell survival properties manifest exclusively in the context of abnormal AIMP2 accumulation, devoid of any tumorigenic effects. This suggests that DX2 could represent a distinctive therapeutic target for addressing Parkinson's disease in patients.